El equilibrista desorientado: la dinámica evolutiva de las cláusulas contractuales en contratos predispuestos y el mito de la baja calidad de los contratos de consumo - Rodríguez García, Gustavo Manuel (2015)
The standard-form agreements, pejoratively labeled as “adhesion contracts”, have bad reputation. A significant number of academics and most of consumer protection authorities often believe that the absence of negotiation and the preponderance of rights and benefits assigned to suppliers (versus costs, obligations or limitations imposed to consumers) show a kind/ sort of abuse against an alleged weak party of the consumption relationship. In this article, Professor Rodríguez García states that the skeptic and hostile vision regarding the standard-form agreements is wrong and is based on a poor understanding of the incentives and purposes that this type of contractingfulfills. On the contrary, the author intends to state that the control of clauses included in  consumption contracts  is prejudicial to consumers. Therefore,this is a control type that should be removed from the legal system.